Arduino based voice controlled wheelchair. (January 2020) - Kian Hou, Tan; Yagasena; Chelladurai
Abstract: A voice controlled wheelchair prototype was developed using a commercially available manual wheelchair to assist people with both upper and lower limb disabilities. An Arduino microcontroller processes the voice command from the speech recognition module and controls the motor movement of the wheelchair. Bluetooth module was also used to do away with messy wiring and an optional joystick command was also incorporated into the prototype design. The success rate of the wheelchair to recognize the voice commands in English, Chinese and Malay was high. The overall cost of the prototype was kept low to make it affordable.